PENGARUH PEMASARAN MEDIA SOSIAL DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN DI KAGUMI KOPI NUSANTARA KABUPATEN SUKABUMI - Diana Adi Rahmasari; Sudarijati; Endang Silaningsih (Jurnal Visionida, 2023)
The purpose of this research is to find out consumer responses and analyze the influence of social media marketing and lifestyle on purchasing decisions. The research method used is multiple linear regression analysis, and 100 customers are used as a sample using the sample methodnon probability sampling procedureaccidental sampling. The research results show that social media marketing and lifestyle variables simultaneously and partially have a positive and significant influence on purchasing decisions. The benefits for writers, academic environment companies are as learning, references and strategies in decision making.